The Development of 6Cs Skills through Project-Based Learning ‘Masyarakat Belajar Sejarah’ (History Learning Society) - Michael Sylvester Mitchel Vinco; Rizal Izmi Kusumawijaya; Fathimah Dayaning Pertiwi; Nurul Septia Salsabila; Riski Eka Oktavianengrum (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: This study aims to develop students’ 6Cs skills—critical thinking, creativity, communication, collaboration, character/compassion, and citizenship/culture—through the implementation of Project-Based Learning (PjBL) in a program titled Masyarakat Belajar Sejarah (History Learning Society). The research responds to the relatively low competitiveness of students in East Kalimantan amid the challenges of the 21st-century VUCA world, Indonesia’s demographic bonus, and the development of the new national capital (IKN) in East Kalimantan. Using Kemmis & McTaggart’s action research model, the study involved students from the History Education Program, FKIP, Mulawarman University, across three cohorts (2020–2022). Data was collected through observation, documentation, questionnaires, and interviews in March and June 2023. Students collaborated with schools, non-formal institutions, professionals, and local communities in Samarinda to design creative, contextual historical learning products. The findings show significant improvements across all 6Cs indicators. The project enhanced students’ academic and social competencies and bridged the gap between classroom learning and real-life community engagement. The results highlight the potential of PjBL as a transformative learning strategy for equipping future educators with essential 21st-century skills. This research contributes to history education innovation by positioning students as agents of change within their communities. Abstrak: Penelitian ini bertujuan untuk mengembangkan keterampilan 6Cs mahasiswa—berpikir kritis, kreativitas, komunikasi, kolaborasi, karakter/kepedulian, dan kewargaan/budaya—melalui penerapan model Project-Based Learning (PjBL) dalam program Masyarakat Belajar Sejarah. Penelitian ini dilatarbelakangi oleh rendahnya daya saing mahasiswa di Kalimantan Timur di tengah tantangan dunia abad ke-21 yang ditandai dengan kondisi VUCA (Volatility, Uncertainty, Complexity, Ambiguity), bonus demografi Indonesia, serta pembangunan Ibu Kota Negara (IKN) baru di Kalimantan Timur. Menggunakan model penelitian tindakan Kemmis & McTaggart, subjek penelitian adalah mahasiswa Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman dari angkatan 2020–2022. Pengumpulan data dilakukan melalui observasi, dokumentasi, angket, dan wawancara pada Maret dan Juni 2023. Mahasiswa bekerja sama dengan sekolah, lembaga nonformal, profesional, dan masyarakat Kota Samarinda untuk merancang produk pembelajaran sejarah yang kreatif dan kontekstual. Hasil penelitian menunjukkan peningkatan signifikan pada seluruh indikator 6Cs. Proyek ini tidak hanya meningkatkan kompetensi akademik dan sosial mahasiswa, tetapi juga menjembatani pembelajaran di kelas dengan keterlibatan nyata di masyarakat. Penelitian ini menunjukkan potensi PjBL sebagai strategi pembelajaran transformatif yang relevan untuk membekali calon pendidik dengan keterampilan abad ke-21.